2006
DOI: 10.1002/gcc.20326
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA mutations and mitochondrial DNA depletion in breast cancer

Abstract: Somatic mutations in mitochondrial DNA (mtDNA) have been demonstrated in various tumors, including breast cancer. However, it still remains unclear whether the alterations in mtDNA are related to the clinicopathological features and/or the prognosis in the breast cancer. We analyzed somatic mutations in the D-loop region, the common 4,977-bp deletion, and the copy number of mtDNA in breast cancer and paired nontumorous breast tissues from 60 Taiwanese patients. We found that 18 of the 60 (30%) breast cancers d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
219
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 231 publications
(234 citation statements)
references
References 34 publications
(41 reference statements)
12
219
2
1
Order By: Relevance
“…In a study conducted among 17 Brazilian women, lower levels of mtDNA 4977 mutation were observed in breast cancer tissue than in either the normal control tissue or adjacent normal tissue of breast cancer patients, suggesting that cancer cells are essentially free of this mutation (4). In the second study, a hospital-based study of 60 Taiwanese women with breast cancer, the mtDNA 4977 mutation was detected in 28 non-tumorous breast tissue samples (47%) and only three of the breast cancer samples (5%) (8). In our study, we found the mtDNA 4977 mutation to be ubiquitous in both tumor and non-tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…In a study conducted among 17 Brazilian women, lower levels of mtDNA 4977 mutation were observed in breast cancer tissue than in either the normal control tissue or adjacent normal tissue of breast cancer patients, suggesting that cancer cells are essentially free of this mutation (4). In the second study, a hospital-based study of 60 Taiwanese women with breast cancer, the mtDNA 4977 mutation was detected in 28 non-tumorous breast tissue samples (47%) and only three of the breast cancer samples (5%) (8). In our study, we found the mtDNA 4977 mutation to be ubiquitous in both tumor and non-tumor tissues.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, these PCR methods use an endpoint determination that may not be truly quantitative because of plateau effects (21). There have been some reports demonstrating the advantages of using the real-time PCR method and its potential clinical value for the mtDNA 4977 mutation (8,(18)(19)(20)22). However, only two of these reports used the standard curve method, which is believed to be more reliable and sensitive (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous reports have indicated that the copy number of mtDNA changes in various types of cancer (6)(7)(8)(9)(10)(11)17). In 1989, Yamamoto et al first reported the increased mitochondrial genomic expression in pre-malignant lesions of the colon in patients with pre-cancerous familial polyposis coli (18).…”
Section: A B Cmentioning
confidence: 99%